Analisis Laporan Keuangan Perusahaan Sebagai Penilaian Kinerja Perusahaan (Studi Pustaka pada Perusahaan BUMN Sektor Konstruksi yang Terdaftar di Bursa Efek Indonesia 2020-2022) - Jumiyati; Revita, Maria Lapriska Dian Ela; Sugiarti; Oktiyani, Rina (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The development of the business world in an increasingly open economic situation needs to be based on performance assessment facilities and systems that can encourage companies towards increasing efficiency and competitiveness which will strengthen capital and have an impact on the company's performance assessment. So that it is able and survives in the increasingly tight business competition today. Companies can analyze financial reports, especially in conducting performance assessments. In the research conducted by the author using descriptive qualitative methods and Literature Studies on the financial reports of 4 state-owned construction sector companies listed on the Stock Exchange:  PT Wijaya Karya (Persero) TBK, PT Waskita Karya (Persero) Tbk, PT Adhi Karya Tbk (ADHI), and PT Pembangunan Perumahan (Persero) Tbk. The purpose of this research is to calculate and analyze the Liquidity, Solvency and Profitability of Financial Reports as an assessment of the Company's Performance. The results of the study show that the Liquidity Ratio (current ratio) of PT Waskita Karya (Persero) Tbk has a consistently high current ratio for three consecutive years, with the highest figure in 2020 at 168.89%. This shows the company's ability to meet its short-term obligations better than other companies such as PT Wijaya Karya (Persero) Tbk and PT Adhi Karya (Persero) Tbk which have lower ratios. The solvency ratio of PT Waskita Karya (Persero) Tbk also stands out with a very high debt to equity ratio, reaching 979.55% in 2022. This indicates that the company is highly dependent on debt in its funding structure. High dependence on debt can increase financial risk, Profitability Ratio, PT Wijaya Karya (Persero) TBK and PT Waskita Karya (Persero) Tbk showed an increase in Net Profit Margin, which indicates an improvement in operational efficiency and management. On the other hand, PT Adhi Karya (Persero) Tbk and PT Pembangunan Perumahan (Persero) Tbk experienced a decline in margin, although they maintained a positive margin. Different receivable turnover ratios also provide an overview of the efficiency of receivables management in these companies. PT Wijaya Karya (Persero) Tbk for example, in 2021 had a very high receivables turnover ratio of 790.28%, indicating that this company is able to manage receivables very efficiently, accelerating cash collection from credit sales.